(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to study the role of the Scurm and Kanban framework in achieving sustainable development. In the audit and internal control departments of (6) private banks listed in the Iraq Stock Exchange, which number (69) banks, after reviewing the periodic reports prepared by the Central Bank of Iraq. The researchers reached a set of conclusions, the most important of which is the existence of applications of lean internal auditing methods in the local environment of the research sample banks, and the concept and framework related to the paragraph (the head of Scurm meets the lean internal audit team and stakeholders to decide the next activity to start with, auditing and planning to set the required goals) ) By the research sample banks, and it is possible to apply the lean internal audit in other economic units in the local environment, despite the existence of obstacles to its application, as it adds value to the work of the team and brings about a change in the method of work of the team, in addition to reducing the time for the traditional audit process and continuous follow-up in identifying problems and risks immediately Its emergence, and this opens a new way in applying this method of internal auditing in other economic units for the first time The researchers presented a set of recommendations, the most important of which is the need to pay attention to knowing the concept and framework of Scurm and to hold training courses on the Scurm framework and Scurm master in the research sample banks due to the lack of sufficient knowledge of this concept and framework and the interest in the accumulated reports prepared by the lean internal audit team in Their method of work because it has an important role in determining which elements, activities and steps add value and excluding the elements, activities and steps that do not add value and the need to pay attention to holding training courses on the most important lean internal audit frameworks (Scurm framework and Kanban framework) and explaining the essence of the work of each framework and what Focuses on each framework and any framework that is the core method of the method of work of lean internal audit.